PERAN GENDER DAN PENALARAN MORAL DALAM PENGAMBILAN KEPUTUSAN ETIS DI BIDANG MANAJEMEN DAN IMPLIKASINYA: STUDI KASUS PADA ORGANISASI NIRLABA - ., Djuwari; Suryani, Tatik (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2005)
How to make ethical decision making is very important in many aspect managerial process, because its implication can impact many other activities. Research found that many unethical behavior in business process is caused by unethical decision making. The recent research indicates that gender has important role in decision making process. The research is aimed to examine the effects of gender in decision making process in management. Beside it, the research also wants to examine the influence of moral reasoning to ethical decision making. Research involved 105 respondent from many non profit organizations located in East Java. By using t-test, the result reveals that there is significant difference between women and man in decision making. Women more ethical in decision making than men, in some aspect. Women more commit to autonomy, equality, win-win principle and moral integrity. By using simple regression analysis, the result indicates that moral reasoning influences significantly to ethical decision making. This research support the previously research that is conducted by Glover (2002) which the culture setting similarly with this research. The result can't be separated by the Indonesia cultural that expect women more ethical, obedience and respect to moral value.